Aliguliyev, Ramiz - (:unkn) unknown (My University, 2025)
Corresponding member of Azerbaijan National Academy of Sciences (ANAS), Baku, Azerbaijan 2011, DSc in Information Technology (System Analysis, Control and Information Processing), Institute of Cybernetics (now Institute of Control Systems) of ANAS, Baku, Azerbaijan. 2002, PhD in Mathematics (Differential Equations), Institute of Mathematics and Mechanics of ANAS, Baku, Azerbaijan1983, BSc, MSc in Applied Mathematics, Baku State University, Baku, Azerbaijan